2008
DOI: 10.1161/circulationaha.108.780031
|View full text |Cite
|
Sign up to set email alerts
|

Local Tenomodulin Absence, Angiogenesis, and Matrix Metalloproteinase Activation Are Associated With the Rupture of the Chordae Tendineae Cordis

Abstract: Background-Rupture of the chordae tendineae cordis (CTC) is a well-known cause of mitral regurgitation. Despite its importance, the mechanisms by which the CTC is protected and the cause of its rupture remain unknown. CTC is an avascular tissue. We investigated the molecular mechanisms underlying the avascularity of CTC and the correlation between avascularity and CTC rupture. Methods and Results-We found that tenomodulin, which is a recently isolated antiangiogenic factor, was expressed abundantly in the elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 34 publications
7
52
0
Order By: Relevance
“…Tenomodulin is a structural protein that has been shown to be essential for tendon maturation (Docheva et al 2005) and maintenance of tendon integrity as shown for tendon cells in the eye (Kimura et al 2008). Tendon tissue principally is very little vascularised and tenomodulin seems a critical factor that regulates the neoformation of vessels (Shukunami et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Tenomodulin is a structural protein that has been shown to be essential for tendon maturation (Docheva et al 2005) and maintenance of tendon integrity as shown for tendon cells in the eye (Kimura et al 2008). Tendon tissue principally is very little vascularised and tenomodulin seems a critical factor that regulates the neoformation of vessels (Shukunami et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…We reported that Scx positively regulates the expression of Tnmd, which has anti-angiogenic activity in its C-terminal cysteinerich domain (Kimura et al, 2008;Oshima et al, 2004). In contrast to ligaments responsible for bone-to-bone connections, the PDL, localized between the alveolar bone and the cementum of the tooth, is exceptionally well vascularized, reflecting the high metabolic turnover of cellular and extracellular constituents.…”
Section: Inhibitory Action Of Scx On Mineralization Of the Ecm Of Pdlmentioning
confidence: 99%
“…In contrast, angiogenesis and VEGF expression are increased in calcified aortic valves (21,22). Previously, we showed that chondromodulin I (encoded by Lect1) and tenomodulin, angioinhibitory factors expressed in the cartilage and tendon, respectively, were expressed in the cardiac valves and chordae tendineae cordis (23,24), respectively. Whereas chondromodulin I was expressed in the normal cardiac valves, its expression was diminished in areas of angiogenesis in the degenerated valves of human VHD.…”
Section: Introductionmentioning
confidence: 98%